Criteria for selecting typical representatives of reinforced concrete products for certification fire resistance tests - Nekhan’ Денис Сергеевич; Palevoda Иван Иванович; Zaynudinova Наталья Владимировна; Ivlev Юрий Петрович; Botyan Сергей Сергеевич; Lishay Игорь Леонидович (Journal of Civil Protection, 2025)
Purpose. To establish criteria for selecting typical representatives of reinforced concrete products for testing to determine the fire resistance during conformity assessment procedures for technical requirements. Methods. Generalization of approaches to the extention of the results of fire resistance tests of building structures and theoretical methods for assessing fire resistance of building structures. Analysis of the influence of quantitative and qualitative indicators of reinforced concrete products on their theoretical fire re-sistance, as well as the results of fire tests, including the extention of fire test results. Findings. An algorithm has been developed and criteria for selecting typical representatives of reinforced concrete products for fire resistance certification tests have been defined, based on a comprehensive analysis of simplified methods and existing tabular data on fire resistance assessment. Their application makes it possible to ensure fire safety of buildings by selecting a reinforced concrete product for fire resistance certification tests, the structural and design features of which indicate that it potentially has the lowest fire resistance of all products in the series. Application field of research. The obtained results can be used in the design of reinforced concrete structures, as well as in the design of buildings and structures. Certification bodies can use the obtained results within the framework of assessment (confirmation) of conformity of a series of reinforced concrete products to technical requirements when selecting typical representatives of reinforced concrete products for testing. The results obtained in the present work are included in the «Regulations on the selection of typical representatives of reinforced concrete products for testing to determine strength, stiffness, crack resistance, fire resistance during conformity assessment procedures».